2000
DOI: 10.5511/plantbiotechnology.17.235
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous DNA Uptake via Cellular Permeabilization and Expression of Foreign Gene in Wheat Zygotic Embryos.

Abstract: Exogenous DNA uptake and transient expression of the GUS reporter gene was studied in wheat (Triticum aestivum L.) zygotic embryos employing a simple procedure of cellular permeabilization by membrane interactive agents like saponin and toluene. Uptake of expression vectors with different promoters was detected in mature and immature embryos. The frequency of GUS expression was detected to be higher in mature embryos than immature embryos probably due to a certain degree of disorganization of the plasmalemma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Peptide synthesis and fluorophore labelling Peptides (Table 1) [26,[50][51][52][53] were custom synthesised and fluoresceinated at the N-terminal amino group (Alberta Peptide Institute, Edmonton, Canada). FITC-dextran sulfate (4 kDa; Sigma Aldrich, Oakville, Canada) served as a nonpeptidic negative control in the initial experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptide synthesis and fluorophore labelling Peptides (Table 1) [26,[50][51][52][53] were custom synthesised and fluoresceinated at the N-terminal amino group (Alberta Peptide Institute, Edmonton, Canada). FITC-dextran sulfate (4 kDa; Sigma Aldrich, Oakville, Canada) served as a nonpeptidic negative control in the initial experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorimetric analysis also indicated that transportan had relatively more penetration ability in the nonpermeabilized embryos than the Tat peptides and pVEC; nonetheless, an increase in uptake of labeled transportan (1.9-fold) was also observed in the embryos subjected to permeabilization treatment. Fluorescence uptake for negative controls [M-Tat and fluorescein isothiocyanate (FITC)-dextran sulfate] also doubled in permeabilized embryos but their relative fluorescence uptake level remained [53] significantly lower than the other CPPs investigated (Fig. 1B).…”
Section: Cellular Uptake Of Cpps Is Enhanced Remarkably By Permeabilimentioning
confidence: 98%
See 1 more Smart Citation
“…Although most regeneration studies in wheat have been confined to immature embryos, scutellum and also to immature inflorescence tissue (Patnaik & Khurana, 2001), nonetheless, mature embryos have also been employed for callusing, regeneration and transformation studies (Mahalakshmi et al, 2000;Patnaik & Khurana, 2001;Khurana et al, 2002). Ozgen et al (1996a, b) appraised the callusing response of mature and immature embryos of seven genotypes of winter durum wheat cultured on MS medium supplemented with 2,4-D and found that mature embryos had low frequency of callus formation but a high regeneration capacity in comparison with immature embryos.…”
Section: Generation Of Pin2 Transgenic Plantsmentioning
confidence: 98%
“…Recently, Mahalakshmi et al (2000) exploited the altered membrane characteristics of dry tissues and coupled it with the use of membrane permeabilizing substances like saponin, toluene, triton, etc. ; and reported gus gene expression in mechanically isolated seed-derived dry embryos of wheat by incubating in a buffer containing plasmid DNA along with various membrane permeabilizing agents.…”
Section: Alternative Approachesmentioning
confidence: 99%